THE RELATIONSHIP BETWEEN LIFESTYLE AND THE INCIDENCE OF HYPERTENSION AT PRIMA HEALTH CENTER IN GUDANG VILLAGE SITUBONDO - Soleha, Rinta Amaliatus; Basri, Achmad Ali; Wildan, Moh; Purnama, Yugi Hari Chandra (LPPM Universitas dr. Soebandi, 2025)
Introduction: Hypertension commonly occurs in middle-aged to elderly individuals and, if left untreated, can lead to fatal outcomes. It is often triggered by lifestyle factors such as physical inactivity, poor diet, lack of sleep, and smoking. Purpose: This study aimed to examine the relationship between lifestyle and the incidence of hypertension at the Prima Health Center in Gudang Village, Situbondo Regency. Methods: A cross-sectional correlational design was used. The study population consisted of 130 individuals, with a sample of 98 hypertensive patients selected through stratified sampling. Data were collected using a lifestyle questionnaire and observation sheet. Univariate analysis was conducted using frequency and percentage, while bivariate analysis used the Spearman rank test. Results: The majority (62.3%) of respondents had unhealthy lifestyles, and most (58.2%) were diagnosed with stage one hypertension. The Spearman rank test showed a p-value of 0.001 ≤ 0.05, indicating a significant correlation. The contingency coefficient of 0.538 suggests a moderate relationship between lifestyle and hypertension. Conclusion: Unhealthy lifestyles are associated with higher stages of hypertension. A significant correlation exists between lifestyle and the incidence of hypertension in Gudang Village